Human mesenchymal stem cells as delivery of osteoprotegerin gene: homing and therapeutic effect for osteosarcoma - Qiao B; Shui W; Cai L; Guo SQ; Jiang DM (Dove Medical Press, 2015)
Bo Qiao, Wei Shui, Li Cai, Shuquan Guo, Dianming Jiang Department of Orthopaedics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China Abstract: Biological treatments have been studied extensively and previous studies have proved that osteoprotegerin (OPG) can inhibit the development and progress of human osteosarcoma. However, the utility of biologic agents for cancer therapy has a short half-life, which can hardly deliver to and function in tumor sites efficiently. Mesenchymal stem cells (MSCs) have the potential to migrate to tumor sites. In this study, MSCs transfected with adenoviruses carrying the OPG gene (MSCs-OPG) were used via the tail vein to treat athymic nude mice (nu/nu) bearing osteosarcoma. In vivo and ex vivo images were used to validate the MSCs homing to tumors. The therapeutic effect for osteosarcoma was evaluated by observations on growth of tumors and bone destruction. The results showed that infected MSCs-OPG labeled with red fluorescent protein (RFP) can migrate to tumor sites and express OPG protein. The treatment by MSCs-OPG reduced the tumor growth and inhibited bone destruction in vivo. All these indicated that MSCs can deliver OPG to tumor sites, which could be a new direction of biological treatment for human osteosarcoma. Keywords: therapy, MSC, OPG, bone tumor